2015
DOI: 10.1111/ajo.12382
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the use of the Myosure resectoscope to manage endometrial polyps in an outpatient setting

Abstract: Background: The Myosure resectoscope has been in use since 2009. Our unit is the first in Australia to describe the use of the Myosure device in the outpatient setting to resect endometrial polyps. Aim: To compare patient satisfaction and pain scores of pre-and postmenopausal women undergoing outpatient removal of endometrial polyps using the Myosure device. Material and Methods: Public hospital based prospective study. Patients (n=42) who opted to have resection of endometrial polyps under local anaethesia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This is in contrast to most findings that suggest that postmenopausal status is related to a higher pain score in hysteroscopy, which is attributed to a tighter cervical os and vaginal dryness from a hypo-oestrogenic state 15 . However, our results are in line with those in a study that reported significantly higher pain scores in premenopausal women than in postmenopausal women (3.2 vs 2.5, p=0.047) who underwent removal of endometrial polyps in an outpatient setting using the MyoSure morcellation device 16 . One explanation for this observation may be that pain receptors in the cervix or uterus are more sensitive in premenopausal women, and that the co-existence of adenomyosis, fibroids, and chronic inflammatory pelvic conditions is more common in premenopausal women 17 .…”
Section: Discussionsupporting
confidence: 92%
“…This is in contrast to most findings that suggest that postmenopausal status is related to a higher pain score in hysteroscopy, which is attributed to a tighter cervical os and vaginal dryness from a hypo-oestrogenic state 15 . However, our results are in line with those in a study that reported significantly higher pain scores in premenopausal women than in postmenopausal women (3.2 vs 2.5, p=0.047) who underwent removal of endometrial polyps in an outpatient setting using the MyoSure morcellation device 16 . One explanation for this observation may be that pain receptors in the cervix or uterus are more sensitive in premenopausal women, and that the co-existence of adenomyosis, fibroids, and chronic inflammatory pelvic conditions is more common in premenopausal women 17 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present series, a day case theater setting was used because the hospitals have yet to acquire the capacity and required skills for outpatient operative hysteroscopy. Various tools are available for the resection of polyps, including a monopolar loop electrode, scissors and graspers, bipolar systems, laser systems, a mechanical energy system, morcellators, and tissue‐assimilation systems . In the present series, a combination of scissors, graspers, and monopolar resectoscope was used.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly over the last decade, more operative hysteroscopic procedures have been performed in an office-based setting. Mcilwaine et al showed in a study of 42 patients that the Myosure lite device (uses electromechanical energy) can be successfully used to resect small fibroids in the outpatient setting with a high level of patient satisfaction with the use of local anaesthetic in a paracervical block [40].…”
Section: Anaesthesiamentioning
confidence: 99%